2019
DOI: 10.3390/mi10060416
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-Based Wavelength-Selective Bolometers

Abstract: We propose and experimentally demonstrate a compact design for membrane-supported wavelength-selective infrared (IR) bolometers. The proposed bolometer device is composed of wavelength-selective absorbers functioning as the efficient spectroscopic IR light-to-heat transducers that make the amorphous silicon (a-Si) bolometers respond at the desired resonance wavelengths. The proposed devices with specific resonances are first numerically simulated to obtain the optimal geometrical parameters and then experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Besides, most of the existing incandescent infrared sources suffer from several shortcomings, such as limited wavelength range, lifetime, and sensitivity to flammable gasses. In addition, as an alternative infrared source, the microelectromechanical systems (MEMS) based silicon thermal emitters depict relatively slow response (~1 kHz maximum modulation frequency) because of their slow responsivity characteristics with few mV/W [ 74 ]. Besides, the fundamental limitation of semiconductor-based light-emitting diode (LED) has the advantage of high modulation speed at IR (infrared) ranges [ 75 ].…”
Section: Graphene-based Thermal Emittersmentioning
confidence: 99%
“…Besides, most of the existing incandescent infrared sources suffer from several shortcomings, such as limited wavelength range, lifetime, and sensitivity to flammable gasses. In addition, as an alternative infrared source, the microelectromechanical systems (MEMS) based silicon thermal emitters depict relatively slow response (~1 kHz maximum modulation frequency) because of their slow responsivity characteristics with few mV/W [ 74 ]. Besides, the fundamental limitation of semiconductor-based light-emitting diode (LED) has the advantage of high modulation speed at IR (infrared) ranges [ 75 ].…”
Section: Graphene-based Thermal Emittersmentioning
confidence: 99%
“…Many contributions to temperature sensors and temperature imagers are available in the corresponding technical literature. Regarding the uncooled thermal image sensors, some papers present contributions considering area reduction, enhancement of responsivity and sensitivity, signal readout process, image processing, power consumption and noise equivalent temperature difference (NETD) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. It is desirable to have these sensors integrated into standard CMOS technology to reduce the costs and to facilitate embedding the interface and the readout electronic circuitry [ 1 , 2 , 4 , 5 , 7 , 10 , 11 , 12 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most temperature sensors are available for MEMS -based microscale measurements, and not all of them have the desired integration with the CMOS technology, to feature essential functions such as amplification and signal conditioning [ 11 , 15 , 17 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Furthermore, there have been developments in the nanoscale thermal sensing [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dao et al have demonstrated a compact design for membrane-supported, wavelength-selective infrared (IR) bolometers [ 1 ]. The fabricated devices exhibit a wide resonance tunability in the mid-wavelength IR atmospheric window by changing the size of the resonator of the devices, evidencing that the concept of the proposed wavelength-selective IR bolometers is realizable.…”
mentioning
confidence: 99%